Identifying significant elements of the digital transformation of organizations in Kuwait - Abdullah Alshehab; Thalaya Alfozan; Hesham F. Gaderrab; Mohammad Abdulateef Alahmad; Abdulrahman Alkandari (Institute of Advanced Engineering and Science, 2022)
The adoption and implementation of digital transformation (DT) plans and initiatives have become compulsory for organizations worldwide during this flourishing era of advanced technology. However, it is estimated that 70% of all DT initiatives do not achieve their goals, with billions of dollars going to waste. This study identified the main elements of digital transformation initiatives from the literature by scholars around the world and then applied these elements to organizations in Kuwait. 33 organizations (private and public) in Kuwait participated in a survey to investigate the level of readiness of organizations attempting to execute digital transformation plans and initiatives. Some insights were found: having a well-defined strategic vision in organizations, digital leadership, technical talent, and having digital expertise are significant elements in implementing digital transformation plans.